2022
DOI: 10.17221/78/2021-rae
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electric field treatment for the stimulation of microorganisms: Applications in food production

Abstract: The pulsed electric field (PEF) technology is a non-thermal processing technique usually used for microbial inactivation in food industries. The application of this technology at sub-lethal levels prior to or during the fermentation processes enhances the mass transfer and cell permeability. It could also cause changes in the genetic, metabolic, and physiological responses of microbial strains leading to an improvement in the fermentation process. Several studies reported the benefits of PEF on microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…It was reported that the application of PEF before the fermentation process increases cell permeability and mass transfer, thus reducing the fermentation time. 33 At the end of the fermentation (14th day), the pH values of the samples were determined as 3.39 ± 0.03 and 3.33 ± 0.06 for the control and PEF-treated samples, respectively (Fig. 1(A)).…”
Section: Resultsmentioning
confidence: 98%
“…It was reported that the application of PEF before the fermentation process increases cell permeability and mass transfer, thus reducing the fermentation time. 33 At the end of the fermentation (14th day), the pH values of the samples were determined as 3.39 ± 0.03 and 3.33 ± 0.06 for the control and PEF-treated samples, respectively (Fig. 1(A)).…”
Section: Resultsmentioning
confidence: 98%
“…The concepts reflected in the definition of emerging technology have criteria including rapid recent growth, in the process of transition and/or change, market or economic potential that has not been fully exploited, and increasingly science-based (Cozzens et al 2010). Emerging technologies have made significant strides in recent years, with pulse electric field (PEF), moderate electric field (MEF), ohmic heating, ultrasound, cold plasma, and other methods demonstrating potential for a wide range of applications (Chizoba Ekezie et al 2017;Gavahian and Tiwari 2020;Bhargava et al 2021;El Kantar and Koubaa 2022;Parniakov et al 2022;Vorobiev and Lebovka Supported by the National Research and Innovation Agency-Indonesia (Grant No. B-169/III/PR.03/5/2021).…”
mentioning
confidence: 99%